Investigating the Effect of Mid-Term of Aerobic Exercise on Apoptosis Biomarkers in the Cardiomyocytes of Streptozotocin-Induced Diabetic Rats - Saeed Tanoorsaz; Naser Behpour; Vahid Tadibi (Fasa University of Medical Sciences, 2017)
Background & Objective: Apoptosis plays a major role in the process of diabetes-induced heart disease, but the effects of aerobic intermediate exercises on the status of apoptosis in diabetics' cardiomyocytes are unclear. The aim of this study was to investigate the effect of 4-week aerobic exercise on apoptosis biomarkers in the cardiomyocytes of Streptozotocin-induced diabetic rats. Material&Methods: 40 adult rats were randomly assigned to 4 groups, including: Control, Control¬+¬Diabetes, Exercise and Exercise + Diabetes. To induce diabetes intraperitoneal injection of Streptozotocin (STZ) solution (55mg/kg) was used. 14 days after STZ injection, the level of fasting blood glucose was measured by a glucometer. After confirming diabetes induction, the exercise protocol was performed for 4 weeks. The training groups ran for 4 weeks (5sessions/week) at a speed of 15-18 m/min and 25 to 44 minutes. 48 hours after the last training session, the subjects were anesthetized and the cardiac muscle was removed. The sFas, FasL and Bcl-2 were measured by ELISA. Results: Induction of diabetes in the control group, resulted in a significant increase in sFas and FasL levels and insignificantly increase in sFas/FasL and also insignificantly decrease in Bcl-2 levels (p<0.05).In non-diabetic groups, the implementation of 4 weeks of exercise training resulted in a significant decrease in sFas, FasL and a significant reduction of sFas/FasL and a significant increase in Bcl-2(p<0.05). Performing of 4 weeks of exercise training in diabetic groups also led to a nonsignificant decrease in sFas and sFas/FasL and a significant decrease in FasL and a nonsignificant increase in Bcl-2. Conclusion: The present study confirms the progressive effect of diabetes-induced apoptosis on heart. The results suggest that regular aerobic exercises may be used as a non-pharmacological strategy to reduce the complications of diabetes-induced apoptosis in the heart tissue of diabetic people.